The effects of classroom acoustic quality on student perception and wellbeing: a systematic review across educational levels - Alice Mercugliano; Arianna Corbani; Lucia Bigozzi; Giulia Vettori; Oriana Incognito; Oriana Incognito (Frontiers in Psychology)
The acoustic quality of the school environment is crucial in enhancing learning and contributing to classroom wellbeing. The aim of this systematic review was 2-fold: (1) to investigate students' perspectives on listening in different learning contexts, with a focus on noise and reverberation in the classroom; and (2) to investigate the impact of indoor acoustic quality and reverberation on wellbeing. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) procedures to identify peer-reviewed studies, 12 studies met the inclusion criteria. Methodological quality was assessed using an existing framework. The results highlight an age-related progression in acoustic awareness from preschool children with limited differentiation to older students with refined perceptions. The impact of acoustics on wellbeing extends beyond learning to social relationships, motivation, and engagement, with older students exhibiting greater sensitivity than younger students. A research gap exists in preschool settings owing to methodological challenges in assessing young children's experiences. This review highlights the need for improved acoustic standards, tailored interventions, and awareness programmes to improve learning environments and wellbeing.